Preoperative timed single leg standing time is associated with the postoperative activity of daily living in aged disabled patients with end-stage knee osteoarthritis at six-months after undergoing total knee arthroplasty. Issue 2 (4th March 2017) - Sugawara, Yu; Ishijima, Muneaki; Kurosawa, Hisashi; Shimura, Yukio; Kaneko, Haruka; Liu, Lizu; Futami, Ippei; Iwase, Yoshiyuki; Kaneko, Kazuo
Abstract: Objectives : The aim of the present study was to investigate the effect size (ES) of total knee arthroplasty (TKA) for the symptoms and lower limb function and identify preoperative factor(s) associated with the post-operative activity of daily living (ADL) in aged patients with end-stage knee OA undergoing TKA. Methods : Fifty-nine aged patients with end-stage knee OA (mean age: 74.6 years) were enrolled in this study. The symptoms and lower limb function of the patients were evaluated using the Japanese Knee Osteoarthritis Measure (JKOM), the timed up and go (TUG) test and timed single-legged stance test with eyes open (TSLS) before and after six months from the operation. Results : While the ES of TKA for the improvement of pain was 2.83, the ES of TKA for the improvement of ADL, TUG and TSLS were 1.30, 0.59, and 0.49, respectively. While the post-operative ADL score was not associated with the preoperative ADL or pain scores, it was associated with the preoperative TUG and TSLS scores. A multiple regression analysis revealed that the one preoperative factor associated with the postoperative ADL was the TSLS. Conclusion : The preoperative TSLS is associated with the postoperative ADL in aged disabled patients with end-stage knee OA.